Notes on Carex (Cyperaceae) from China (VII): new synonyms and imperfectly known species - Jin, Shui-Hu; Lu, Yi-Fei; Chen, Wei-Jie; Jin, Xiao-Feng (Phytotaxa, 2022)
Based on literature survey, examination of type specimens and fieldwork, seven names of Carex are synonymized in the present paper: viz. Carex hypoblephara reduced to a synonym of C. glossostigma; C. dayunshanensis and C. wuyishanensis to synonyms of C. graciliflora; C. dolichogyne to a synonym of C. truncatigluma; C. kwangtoushanica to a synonym of C. tatsiensis; and C. martini to a synonym of C. rhynchophora. The holotype of Carex fokienensis is identified and confirmed at P. The putative endemic species Carex macrosandra (basionym: C. lanceolata var. macrosandra) is synonymized to C. lanceolata, whereas C. cavaleriensis, considered a synonym of the former, is here recognized as a distinct species. A lectotype is designated for C. lanceolata var. macrosandra.